2016
DOI: 10.1038/srep29692
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the transcriptomic response of Fusarium verticillioides in relation to nitrogen availability and the development of sugarcane pokkah boeng disease

Abstract: Pokkah boeng, caused by Fusarium verticillioides, is a serious disease in sugarcane industry. The disease severity is related to the sugarcane genotype as well as environmental considerations, such as nitrogen application. The impact of the nitrogen source (ammonium sulfate, urea, or sodium nitrate) on sugarcane pokkah boeng disease and its pathogen was investigated in planta and fungal growth and sporulation production was measured in vitro. The results showed that ammonium and nitrate were beneficial to fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…7 ). Our results suggested that chronic eutrophication influenced multiple specific biological processes by altering transcription accumulation 40 and coordinating the expression of two aspects of the coral host and Symbiodinium symbionts. However, the mechanisms of global transcriptional changes and their physiological consequences are not yet fully understood.…”
Section: Discussionmentioning
confidence: 78%
“…7 ). Our results suggested that chronic eutrophication influenced multiple specific biological processes by altering transcription accumulation 40 and coordinating the expression of two aspects of the coral host and Symbiodinium symbionts. However, the mechanisms of global transcriptional changes and their physiological consequences are not yet fully understood.…”
Section: Discussionmentioning
confidence: 78%
“…A 2 -ΔΔCt algorithm was used to evaluate the relative fold change in the expression of the each gene using the act1 (actin) gene as an endogenous control. [58, 59] The data were analyzed using LightCycler® 480 software version 1.5.1 (Roche). Pearson’s correlation coefficients were calculated to evaluate the correlation of gene expression obtained by RNA-seq and qRT-PCR using Origin 9.0 software (Origin Lab).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Fusarium verticillioides is a phytopathogenic fungus of economic importance because it is the most commonly reported fungal species that infects maize (32), in addition to causing stalk rot disease in sorghum (33) and Pokkah Boeng disease in sugarcane (34). The diseases caused by Fusarium spp.…”
mentioning
confidence: 99%